Affiliation Of Security And Development (Kesban) Concept And Counterinsurgency Theories (Journal of Namibian Studies : History Politics Culture, 2023)
Global academic intellectuals had come to an agreement that the nexus between security and development is not a new matter of concern.  At the United Nations level, this allegiance has been embellished by denoting that “there is no security without development; there is no development without security.” However, in Malaysia this has been a combative concept applied to prostrate the Communist Party of Malaya (CPM) to surrender their militant business. The concept was inspired from British countermeasures against communist insurgency during the First Malayan Emergency.  Successive to that the Malaysian government formulated security and development concept called “Keselamatan dan Pembangunan” (KESBAN) to pursue the battle against CPM.  The aim of this paper is to analyse the affiliation of KESBAN concept with three leading counterinsurgency theories introduced by Thompson, Galula, and Kilcullen. The paper will adopt a qualitative approach supported by secondary data in its analysis. The paper will attempt to describe each of the theories vis-à-vis KESBAN concept. The distinctiveness of this concept is that it has vast similarity with the famous counterinsurgency theories. The finding had established that KESBAN concept and the highlighted counterinsurgency theories correspond as a counterinsurgency framework capable to fight an insurgency.